Religious Moderation Values in the Subject of Islamic Religious Education and Budi Pekerti Class IX Junior High School - Haulid Haulid; Syukri Syukri (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2023)
Religious moderation is a government programme aimed to avert religious misconceptions, countering extremism, and foster concord within Indonesia's varied and multicultural society. This article describes the values of religious moderation in the Islamic Religious Education and Cultivation textbooks for Junior High School students. The research method employed for this study is library research. Data collection was conducted through a review of the Islamic Religious Education and Budi Pekerti textbooks for year 9 junior high school students, published by the Ministry of Education and Culture in 2018. Content analysis and discourse analysis were employed for data analysis. The research findings revealed that the textbook for Islamic Religious Education and Budi Pekerti class IX demonstrated four values associated with religious moderation: non-violence, deliberation, accommodation of local culture, and tolerance. This study has the potential to enhance the promotion of religious moderation values in Indonesian education. Abstrak: Moderasi beragama adalah sebagai salah satu program pemerintah untuk menghadapi ekstremisme, pemahaman keagamaan yang menyimpang dan mempromosikan harmoni dalam masyarakat yang beragam dan multikultural di Indonesia. Artikel ini bertujuan untuk mendeskripsikan nilai-nilai moderasi beragama pada buku teks siswa mata pelajaran Pendidikan Agama Islam dan Budi Pekerti Jenjang Sekolah Menengah Pertama. Metode penelitian menggunakan jenis penelitian library research. Pengumpulan data dilakukan dengan menelaah dokumen buku teks mata pelajaran PAI dan Budi Pekerti kelas IX SMP terbitan Kemendikbud Tahun 2018. Teknik analisis data menggunakan analisis isi dan analisis wacana. Hasil penelitian menunjukan nilai-nilai moderasi beragama pada buku teks Pendidikan Agama Islam dan Budi Pekerti kelas IX memuat empat nilai, yaitu: anti kekerasan, musyawarah, akomodatif terhadap kebudayaan lokal, dan toleransi. Penelitian ini dapat berkontribusi terhadap penguatan nilai-nilai moderasi beragama dalam pendidikan di Indonesia.